Effectiveness of Schema Therapy on Anxiety and Social Adaptation in Delinquent Adolescents - GhodsiKhorasani , Bahareh; Jouhari , Tina; Moghtaderi , Shabnam; Sabeti, Parasto (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to determine the effectiveness of schema therapy on anxiety and social adaptation in delinquent adolescents in the beautiful city area of Tehran. Methods and Materials: Our research method was a quasi-experimental design with a pre-test and post-test along with a control group and a follow-up phase. The statistical population of this study included all delinquent adolescents registered at the Juvenile Correction and Training Center in the beautiful city area of Tehran in 2021. The sample of this study consisted of 32 male adolescents aged 14 to 18 years, who were selected through purposive sampling. They were then divided into two groups of 16, comprising one experimental group and one control group. The experimental group received 12 sessions of schema therapy. Data were collected using the Social Anxiety Scale for Adolescents (SASA) and the Pike and Wiseman Social Adjustment Questionnaire (1999) and analyzed using repeated measures ANOVA in SPSS22 software. Findings: The results of this study showed that there was a significant difference in social anxiety and social adaptation in the treatment group compared to the pre-test (P < 0.05). Also, a significant difference was observed in the follow-up phase compared to the pre-test (P < 0.01). However, no significant difference was observed in the follow-up phase compared to the post-test (P > 0.05). Conclusion: The results indicate that schema therapy can be effective in reducing anxiety and improving social adaptation in delinquent adolescents.